Nilai Toleransi Dalam Perspektif Hukum - Nursamsi Nursamsi (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2023)
The hope for religious harmony in life is harmony between religious believers in the spirit of mutual understanding, understanding one another. . This article aims to introduce more deeply the limits of religious tolerance from a legal perspective. The analysis used in this research is descriptive analysis. The data is classified and then adjusted according to the study sequentially. For this reason, researchers use books, or journals and research results related to this article. The results of this research show that the limits of tolerance in the Islamic view are that humans are social creatures who are of course required to interact with other individuals, even Islam provides a clear domain. Including in interacting, of course always prioritizing respect, not tearing each other down, staying within the corridor limits determined in Islamic religious law.